Clinical Outcome of Phacoemulsification with Multifocal Intra Ocular Lens in a Tertiary Eye Care Centre : DOI: https://doi.org/10.46405/ejms.v6i9.553 - Singh , Sanjay Kumar; Mandal , Jayshree; Sanyam , Sandip Das; Bista, Bipin; Dulal , Sunu (Europasian Journal of Medical Sciences, 2024)
Background: Cataract remains the leading cause of blindness globally, and phacoemulsification surgery has emerged as a standard treatment. Monofocal intraocular lenses (IOLs) provide good distance vision but do not accommodate near and intermediate distances, necessitating spectacle use. Multifocal IOLs offer pseudo-accommodation for enhanced visual function but may be associated with photopic symptoms. This study assesses the clinical effectiveness of multifocal IOL implantation, evaluating visual outcomes, spectacle independence, and photopic symptoms. Data & Methods: A retrospective observational study was conducted at a tertiary eye care center over two years. Patients aged 18 and above with <1.00 D astigmatism who underwent phacoemulsification with multifocal IOL implantation were included. Patients with corneal opacities, prior ocular surgery, or systemic autoimmune conditions were excluded. Uncorrected and best-corrected visual acuity (UCVA, BCVA), near visual acuity, photopic symptoms, and contrast sensitivity were recorded preoperatively and at one-month follow-up. Data were analyzed using SPSS version 24. Results: A total of 40 patients (mean age: 51.31 years; 55% males, 45% females) were included. At one-month follow-up, distance BCVA was 6/6 in 75% of patients, and 90% achieved uncorrected near VA of N6. Only 10% of patients had residual refractive error. No patients reported photopic symptoms. The mean contrast sensitivity score was 1.22 ± 0.31. Conclusion: Multifocal IOL implantation provides effective near and distance vision with high spectacle independence. Proper preoperative counseling regarding patient expectations is crucial to achieving satisfactory outcomes. Further prospective studies with larger sample sizes and longer follow-up are recommended.